Usulan Penjadwalan Perawatan Mesin Filling Secara Preventive Dengan Modularity Design Dan LCC Di PT. Petrosida - Tarisa Nindyas Sari; Endang Pudji W (International Forum of Researchers and Lecturers, 2023)
PT. Petrosida is a manufacturing company engaged in pesticide production. The production system in this company is Make To Order (MTO) where the company will produce products after an order or order from consumers. In its production PT. Petrosida has problems with the main tools used for packaging, one of which is a 1-liter induction semi-automatic filling machine in the herbicide unit, where treatment is carried out after damage to a component. Critical components in filling machines experience an average of 20 times damage in 2022-2023 and the machine maintenance process is still not optimal with an average downtime of 5 hours / month. Therefore, the purpose of research is to be able to carry out preventive maintenance using the modularity design method in the hope that there will be no more breakdowns that hamper the production process so as to reduce machine maintenance costs and to find out the minimum total machine maintenance cost planning using the life cycle cost (LCC) method. By implementing preventive maintenance with modularity design, the total maintenance cost of Rp. 9,747,782 is lower than the company's total maintenance cost of Rp. 23,023,176 with an efficiency rate of 42.3%. And obtained the lowest total life cycle cost of Rp. 340,459,348, - with an optimal life on the machine of 3 years & the number of mechanics one person.